Domestic Abuse: Growth Curve Modeling of Harm Across Repeat Incidents with Police Data - Boyd, Katharine A. (Crime & delinquency, 2025)
This paper analyzes trajectories of harm across repeat domestic abuse (DA) incidents using data from one police force in England and Wales matched with the Crime Harm Index. We use growth curve modeling to identify incident and offender-victim (dyad) predictors of harm. High Incident dyads with four or more DA cases (N = 2,610) have a non-linear decrease in harm across incidents, with distinct trajectories for Intimate Partners and male offenders. The Power Few dyads, the 5% of dyads responsible for 85% of cumulative harm, (N = 133) show a decrease in harm across incidents, with distinct trajectories for DA specialists who are only known to police for DA. While acknowledging the limitations, this study suggests important policy implications.